Mechanical and electrical properties of electrospun PVDF/MWCNT ultrafine fibers using rotating collector - Wang, Shu-Hua (Springer, 2014)
Poly(vinylidene fluoride) (PVDF) ultrafine fibers with different proportions of multi-walled carbon nanotube (MWCNT) embedded have been fabricated using a modified electrospinning device with a rotating collector. With the increasing of MWCNT content, the β phase was noticeable enhanced, and the fibers became more elastic, which was manifested by Young's modulus decreased drastically. Furthermore, with adding the amounts of MWCNTs, the density of carbon nanotube (CNT)-CNT junctions among the fibers increased accordingly. When the MWCNT content was of 1.2 wt.%, a stable three-dimensional conducting network was formed. After this percolation threshold, the density of CNT-CNT junctions among the fibers tended to be a constant quantity, leading to a stabilized conductivity consequently. It is hoped that our results can be helpful for the fabrication of flexible devices, piezoelectric devices, force transducer, and so on. PACS: 81.05.Qk; 81.16.-c